CSR Compensation Cost and Firm Value in Nigeria: Mediating Effect of Liquidity, Moderating Effect of Firm Size, Firm Growth and Business Risk - Idamoyibo, Hwerien Rosemary (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
This work ascertains the influence of the financial aspect of CSR compensation cost on firm value of consumer goods firms in Nigeria for the period 2019-2023. The population consists of the twenty listed consumer goods firms in the Nigerian Exchange Group as of 31st October 2020. Seven of the firms were sampled; secondary data was gathered from the firm’s annual reports for the period of five years. Linear regression was used with the aid of Statistical Package for Social Sciences software 26 to test the hypotheses. The result reveals that the financial aspect of CSR compensation cost has no constructive and substantial influence on Tobin’s q, the mediating effect of the financial aspect of CSR compensation cost has no constructive and substantial influence on liquidity, and the moderating effect of the financial aspect of CSR compensation cost has no constructive and substantial influence on firm size, firm growth, and business risk of the consumer goods firms. The study concludes that the financial aspect of CSR compensation cost has no influence on the firm’s value. The implication of the finding shows that the amount the firms invest in CSR activities for community and society sustainable development was not properly practised; that was why the firms’ financial aspect of CSR compensation costs has no constructive and substantial influence on the Tobin’s q, liquidity, firm size, firm growth and business risk of the firms.